Comparative Safety of Aspiration Thrombectomy Catheters Utilizing Prospective, Active Surveillance of the NCDR CathPCI Registry. Issue 2 (February 2019) - Majithia, Arjun; Matheny, Michael E.; Paulus, Jessica K.; Marinac-Dabic, Danica; Robbins, Susan; Ssemaganda, Henry; Hewitt, Kathleen; Ponirakis, Angelo; Loyo-Berrios, Nilsa; Moussa, Issam; Drozda, Joseph; Normand, Sharon-Lise; et al.
Abstract : Background: Current strategies for ensuring the postmarket safety of medical devices are limited by small sample size and reliance on voluntary reporting of adverse events. Prospective, active surveillance of clinical registries may provide early warnings in the postmarket evaluation of medical device safety but has not been demonstrated in national clinical data registries. Methods and Results: The CathPCI DELTA (Data Extraction and Longitudinal Trend Analysis) study was designed to assess the feasibility of prospective, active safety surveillance of medical devices within a national cardiovascular registry. We sought to assess the ability of our surveillance strategy to avoid false safety alerts by conducting an active safety surveillance study of aspiration thrombectomy catheters using data within the National Cardiovascular Data Registry CathPCI registry, where no difference in safety outcomes were anticipated for the primary in-hospital safety outcome of death and major adverse cardiovascular events (MACE). We performed a propensity-matched analysis of 5 aspiration thrombectomy catheter devices used during percutaneous coronary intervention among 95 925 patients presenting with ST-segment–elevation myocardial infarction between January 1, 2011 and September 30, 2013. After 33 months of surveillance, no safety alerts were triggered for the primary safety endpoints of death or MACE, with no between-catheter differences observed. The absolute risk of death during acute hospitalization ranged from 5.11% to 5.32% among the most commonly used aspiration thrombectomy catheter devices, with relative risks for death ranging from 0.96 to 1.03. The absolute risk of MACE ranged from 9.78% to 10.18%, with relative risks for MACE ranging from 0.99 to 1.02. There were no statistically significant differences in the rates of death or MACE between any of the aspiration thrombectomy catheter devices analyzed. Conclusions: The CathPCI DELTA study demonstrates that prospective, active safety surveillance of national clinical registries is feasible to provide near-real-time safety assessments of new medical devices. Abstract : Supplemental Digital Content is available in the text.